Local governments' responses to the fiscal stress label: the case of New York. Issue 5 (3rd September 2021) - Chung, Il Hwan; Williams, Daniel
ABSTRACT: Fiscal stress has been a source of significant concern for local governments and has led to the introduction of a variety of approaches for dealing with such a situation. One emerging practise is to adopt early-warning systems which identify fiscal stress, assign a fiscal stress label, and assist with local governments' financial management. Although there is a growing body of research focusing on fiscal stress indicators, there is a lack of studies examining whether localities given a fiscal stress label by the fiscal stress monitoring system improve their fiscal health. With a regression discontinuity design, we have found that less stressed localities improve their financial condition as compared with more stressed ones in the short run. This study has the potential to inform discussions about the role and strategies of states in strengthening localities' financial situations and designing a better fiscal monitoring system.